A pathogenic role for cystic fibrosis transmembrane conductance regulator in celiac disease. (28th November 2018) - Villella, Valeria R; Venerando, Andrea; Cozza, Giorgio; Esposito, Speranza; Ferrari, Eleonora; Monzani, Romina; Spinella, Mara C; Oikonomou, Vasilis; Renga, Giorgia; Tosco, Antonella; Rossin, Federica; Guido, Stefano; et al.
Abstract: Intestinal handling of dietary proteins usually prevents local inflammatory and immune responses and promotes oral tolerance. However, in ~ 1% of the world population, gluten proteins from wheat and related cereals trigger an HLA DQ2/8‐restricted TH 1 immune and antibody response leading to celiac disease. Prior epithelial stress and innate immune activation are essential for breaking oral tolerance to the gluten component gliadin. How gliadin subverts host intestinal mucosal defenses remains elusive. Here, we show that the α‐gliadin‐derived LGQQQPFPPQQPY peptide (P31–43) inhibits the function of cystic fibrosis transmembrane conductance regulator (CFTR), an anion channel pivotal for epithelial adaptation to cell‐autonomous or environmental stress. P31–43 binds to, and reduces ATPase activity of, the nucleotide‐binding domain‐1 (NBD1) of CFTR, thus impairing CFTR function. This generates epithelial stress, tissue transglutaminase and inflammasome activation, NF‐κB nuclear translocation and IL‐15 production, that all can be prevented by potentiators of CFTR channel gating. The CFTR potentiator VX‐770 attenuates gliadin‐induced inflammation and promotes a tolerogenic response in gluten‐sensitive mice and cells from celiac patients. Our results unveil a primordial role for CFTR as a central hub orchestrating gliadin activities and identify a novel therapeutic option for celiac disease. Synopsis: The molecular basis for permanent intolerance to dietary cereal proteins and excessive adaptive immune responses in the gut underlying celiac disease have remained unclear. Molecular and genetic approaches now identify the cystic fibrosis transmembrane conductance regulator (CFTR) anion channel as major environmental stress transducer and potential therapeutic target in chronic intestinal inflammation. Constitutive CFTR deficiency in mice increases innate immune response to the gluten component gliadin. Gliadin peptide P31–43 inhibits nucleotide‐binding domain‐1 and ATPase activity of CFTR, impairing its function in intestinal epithelial cells. P31–43‐mediated CFTR inhibition disrupts cellular proteostasis through sustained transglutaminase activation. P31–43‐mediated CFTR inhibition leads to cytoskeleton disassembly, impaired endosomal trafficking, and activation of the inflammasome. Pharmaceutical CFTR potentiators rescue CTFR channel gating and protect from stress‐induction in gluten‐sensitive mice and celiac patient samples. Abstract : Direct inhibition of the CFTR anion channel by dietary wheat peptides can generate the epithelial stress and innate immunity activation that lead to chronic intestinal inflammation.